University students’ perception toward the use of the mother tongue in the EFL classrooms - Siti Hawa; Suryani Suryani; Rini Susiani; Ema Dauyah; A. Halim Majid (Studies in English Language and Education, 2021)
This study identified learners’ perceptions toward using the mother tongue and analyzed the function or occasions of its use in the EFL classroom. A mixed-methods design, employing classroom observation, questionnaire, and semi-structured interview as data collection methods, was used to pursue this study. The questionnaire items gained the students’ opinion on two categories, namely: students’ preference and occasion of mother tongue use. Twenty undergraduate students who took the Speaking course at a private university in Aceh were involved as the participant of the observation and questionnaire. Meanwhile, only three of them were chosen as the interviewee. The questionnaire data were analyzed quantitatively. In contrast, the observation and interview data were analyzed qualitatively. The results indicated that the use of mother tongue brought positive and negative impacts regarding the students’ perception based on their various English proficiency levels. The low level of English proficiency and intermediate students revealed a higher preference toward the mother tongue to understand the instructions, explain unfamiliar vocabularies, and understand the differences or similarities of English pronunciation and idioms. At the same time, the advanced students indicated a negative perception of mother tongue use. They chose to avoid using their mother tongue to improve their skill through maximum exposure to English as the target language in the speaking classroom atmosphere.